FENOMENA GAME ONLINE DALAM KEHIDUPAN SOSIAL KAUM MUDA DALAM PERSPEKTIF HERBERT BLUMER - Irenius Selsus Rengat; Paulinus Sarif; Andi Prayoga (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2022)
Young people are very familiar to online games today. It is indicated by the large number of young people who spend their time just playing online games, thus affecting their social life. The behavior of today's children are not concerned with their environment, but focus on social media and online games. The present research discusses the influence of online games on the social interaction among young people from the perspective of symbolic interactionism according to Hebert Blumer. The research method was qualitative. The data were collected using interviews (involving 4 subjects) and literature studies. The research found out that the young people in St. Parish. Pius X Bengkayang were not addicted to playing online games, online games, but they just killed their spare time. They did within the normal limit in playing online games. Thus, their social interaction with others is still acceptable. Social interaction is important for every human being, to communicate with others. This is a requirement in symbolic interactionism according to Hebert Blumer, namely that there is a relationship between the individual and the community.